116 A CASE REPORT OF ISOLATED CARDIAC LIGHT CHAIN AMYLOIDOSIS WITHOUT HEART FAILURE: AN UNDER-RECOGNISED PRESENTATION. (15th December 2022) - Nuzzi, Vincenzo; Porcari, Aldostefano; Gigli, Marta; Pezzato, Andrea; Zaja, Francesco; Dore, Franca; Bussani, Rossana; Sinagra, Gianfranco; Merlo, Marco
Abstract: Background: Cardiac involvement in light-chain amyloidosis (AL) usually represents a brick in the wall of a multi-system disease. The presence of cardiac deposition of free light chains (FLCs) is the main determinant of survival. Isolated cardiac AL is un uncommon scenario characterised by a challenging diagnostic and therapeutic work-up. Case Summary: A 57-year-old asymptomatic man presented for an incidental finding of myocardial necrosis at the ECG performed for newly-diagnosed arterial hypertension. Alongside signs of previous myocardial infarction, transthoracic echocardiography showed a severely increased left ventricular (LV) wall thickness not consistent with ECG voltages, segmental akinesia with normal LV systolic function with 'apical sparing' pattern. Laboratory assessment showed an unexpectedly high level of natriuretic peptide and persistently abnormal troponin in the absence of symptoms or signs of heart failure or ongoing ischemia. Coronary angiogram confirmed the coronary artery disease. Before revascularization, a complete diagnostic work-up was carried. Serum electrophoresis detected a monoclonal gammopathy that was further investigated by serum immunofixation, revealing high lambda FLCs concentration. Fat pad, bone marrow and salivary glands biopsies resulted negative for amyloid deposition. Finally, endomyocardial biopsy was consistent with AL amyloidosis. Urgent percutaneous revascularization was performed and the patients was timely started on chemotherapy. Discussion: The diagnosis of isolated cardiac AL amyloidosis is challenging and carries important therapeutic implications. As the short-term prognosis might be severely compromised, an accurate diagnostic flow-chart have to be systematically pursued to obtain a precise diagnosis and address the optimal, tailored management.